Dune Field Patterns and Their Control Factors in the Middle Areas of China’s Hexi Corridor Desert - Zhang, Yan; Zhang, Zhengcai (Frontiers in Earth Science, 2022)
The desert areas of China's Hexi Corridor are distributed within or at the edge of oases in a continental river basin in northern China. Recently, researchers had found that rivers can provided sediment material for dunes formation and development, however, this issues had not been more studied. In this study, the relationships between wind energy environment, spatial continental rivers, sand availability and dune field patterns were analyzed in the Hexi Corridor. The wind energy environment can be divided into three regions: the north, an environment with high wind energy; the middle region, with intermediate wind energy; and the south, with low wind energy. The resultant drift potential was predominantly from the NW quadrant. Directional variability of the wind is intermediate in the northern and middle regions, and low in the southern region. The critical wind speed direction was from the SW in the northern region, NW and WNW in the middle region, and NW in the southern region. The wind energy environment controlled the dune field patterns, and the main dune types are barchans, reticulate dunes, star dunes, linear dunes, and coppice dunes, which differ from previous results. Except the wind energy environment, the spatial continental rivers distribution and sand availability were also important for dunes formation and development. Sand dunes were distributed in the downwind of the continental rivers, which confirmed the hypothesis of rivers can provided sediment material for dunes formations.